A Compact Multiband BPF Using Step-impedance Resonators with Interdigital Capacitors - Meesomklin, Suwaluck; Chomtong, Pongsathorn; Akkaraekthalin, Prayoot (Společnost pro radioelektronické inženýrství, 2016)
A compact multiband band-pass filter design for applications of GSM, Wi-MAX and WLAN systems is presented. The design is based on the resonant characteristics of step-impedance and interdigital capacitor resonators with overlap cross coupling structure. The fabricated filter has been operated at the fundamental, first and second harmonic resonant frequencies of 1.8 GHz, 3.7 GHz, and 5.2 GHz, respectively. The experimental results of the fabricated filter agree very well with the simulation expectations using IE3D package. The proposed filter has good performances, while the resonator size can be reduced from λ/2 to λ/8, resulting in the most compact multiband band-pass filter compared with the others using transmission line resonators .
Keywords: Multiband BPF; step-impedance resonator; interdigital capacitor; overlap cross coupling